Cyberculture and the challenges of education in the COVID-19 pandemic (Research, Society and Development, 2022)
This work aims to discuss the influence of cyberculture on today's society and understand how educational technological strategies in the period of the Covid-19 pandemic helped the actors in the process. With this, the various tools used in Brazilian education from 2019 to 2021 were analyzed with the purpose of understanding the benefits for the educational process, in addition to problematizing the consequences brought by poorly planned remote teaching due to the lack of public subsidies and educational project. effective. This process accentuated the teaching crisis, as the result was even greater obstacles in the construction of teaching and learning. The perspective used for the research was bibliographic and qualitative with the premise of capturing the questions that arise in an organized and consistent way. In the debate, authors such as Pierre Lévy (1999) were used to discuss technological advances and, in a perspective of critical analysis of the effects of the digital world, Marx (2017) and Marcuse (2007) were worked.